Sixty years of transthyretin familial amyloid polyneuropathy (TTR-FAP) in Europe: where are we now? A European network approach to defining the epidemiology and management patterns for TTR-FAP. (February 2016) - Parman, Yesim; Adams, David; Obici, Laura; Galán, Lucía; Guergueltcheva, Velina; Suhr, Ole B.; Coelho, Teresa
Abstract : Purpose of review: Transthyretin familial amyloid polyneuropathy (TTR-FAP) is a highly disabling, life-threatening disease characterized by progressive sensorimotor and autonomic neuropathy. The profile of the disease across Europe is inadequately understood at present. Recent findings: The incidence and clinical presentation of TTR-FAP varies widely within Europe, with early and late-onset disease subtypes. In those regions in which the disease is endemic (Portugal, Sweden, Cyprus, and Majorca), a Val30Met substitution in the TTR gene is the predominant genetic cause, whereas in the rest of Europe, cases of TTR-FAP are mainly sporadic with genetic heterogeneity. Current management strategies lack cohesion and patients can experience years of misdiagnosis and suboptimal treatment. Summary: The article aims to disseminate the findings and recommendations from two recent meetings of the European Network for TTR-FAP (ATTReuNET), a panel comprising representatives from 10 European countries (Bulgaria, Cyprus, France, Germany, Italy, the Netherlands, Portugal, Spain, Sweden, and Turkey) with expertise in the diagnosis and management of TTR-FAP. We explore the epidemiology and genetic mark of TTR-FAP across Europe and assess current management strategies, with a view to developing an alternative framework – a networked approach to disease management with an emphasis on collaboration and sharing of best practice. Abstract : Supplemental Digital Content is available in the text